2016
DOI: 10.1016/j.intimp.2015.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of Yinhuapinggan granule on mice with influenza viral pneumonia

Abstract: Yinhuapinggan granule (YHPG), a Chinese medicine granule on the basis of Ma-Huang-Tang (Ephedra Decoction) and the clinical experience of Professor Wan Haitong, has been shown to inhibit the growth of influenza virus in vitro. The aim of this study was to investigate the protective effects of YHPG on mice with influenza viral pneumonia and its effects on regulating related inflammatory cytokines in influenza virus A-infected mice. ICR mice were inoculated intranasally with 15 LD50 viral dose of influenza virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Previous researches have shown that YHPG has distinct antitussive, antiinflammatory and antibacterial effects (He et al 2014;Wan et al 2016). Further, antiviral studies has demonstrated that YHPG has significant effects on ameliorating influenza virus-induced inflammation, inhibiting TLRs/MyD88 mediated NF-jB signalling pathway, and inhibiting influenza virus replication (Peng et al 2016a(Peng et al , 2016b. However, the antiviral effects and its possible mechanism of YHPG in the apoptosis signalling pathway are still obscure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous researches have shown that YHPG has distinct antitussive, antiinflammatory and antibacterial effects (He et al 2014;Wan et al 2016). Further, antiviral studies has demonstrated that YHPG has significant effects on ameliorating influenza virus-induced inflammation, inhibiting TLRs/MyD88 mediated NF-jB signalling pathway, and inhibiting influenza virus replication (Peng et al 2016a(Peng et al , 2016b. However, the antiviral effects and its possible mechanism of YHPG in the apoptosis signalling pathway are still obscure.…”
Section: Discussionmentioning
confidence: 99%
“…According to the traditional dose ratio of 4 (Radix Puerariae Lobatae): 4 (Flos Lonicerae Japonicae): 4 (Polygoni Cuspidati Rhizoma): 2 (Ephedrae Herba): 2 (Armeniacae Semen Amarum): 1 (Glycyrrhizae Radix) ( Supplementary Table 1), YHPG granules were prepared by water-extraction and ethanol-precipitation, and the quality control of YHPG was also performed by HPLC, as reported in our previous research. HPLC analysis was carried out at 210 nm for the determination of eight active components in YHPG, containing L-ephedrine (0.73 mg/g), D-pseudoephedrine (0.407 mg/g), chlorogenic acid (1.92 mg/g), amygdalin (6.37 mg/g), puerarin (4.35 mg/g), polydatin (1.79 mg/g), glycyrrhizic acid (0.692 mg/g) and emodin (0.329 mg/g), respectively (Supplementary Figure 1) (Peng et al 2016a(Peng et al , 2016b.…”
Section: Materials and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Jinhuaqinggan granules are made from Lonicera japonica, herba ephedra (fried honey), gypsum, bitter almond kernel, Scutellaria baicalensis, fructus forsythia, Thunberg Fritillary Bulb, rhizoma anemarrhenae, burdock, Artemisia apiacea, peppermint, and glycyrrhiza [45]. Previous studies regarding the clinical application of Jinhuaqinggan granules were mainly concentrated on the treatment of influenza [46]. It was found that Jinhuaqinggan granules alone, or its combination with oseltamivir both could shorten the time for fever recession in H1N1 patients [47].…”
Section: Jinhuaqinggan Granulesmentioning
confidence: 99%
“…24,25 Ephedra decreased NF-κB p65 activity leading to alleviation of lung damage and regulation of the cytokine production (IL-2 elevation and IL-1β, IFN-γ and TNF-α mRNA inhibition in lung tissues). 26,27 Crataegus azarolus L. (Azarolein English, Za'roor in Arabic), is used in the Greco-Arab traditional medicine to treat cardiovascular diseases, sexual weakness, cancer and diabetes.…”
Section: Introductionmentioning
confidence: 99%